Triggers, transitions, and trip decisions from 1976 to 2019: why utility cyclists in Cape Town choose to ‘ditch their cars’, and why bicycle advocacy says they should - Jennings, Gail (Department of Civil Engineering, 2025)
Almost all cycling research in South Africa to date has focused on utility cyclists living with low incomes, the so-called ‘captive’ user who does not have access to a private car. Individual car drivers (particularly of single occupants), however, are a target of the City of Cape Town’s policy direction, which aims to grow cycling, displacing private travel, to mitigate road traffic congestion and the city’s carbon emissions profile. These utility cyclists with greater mode use options have received comparatively little research attention. Attempts to increase bicycle mode share among this cohort have so far seen little reward. The literature posits that to shift cycling practices in low-cycling countries, there is value in considering the role and influence of narratives of cycling choices, and in understanding what cycling means and why it is already attractive to those who do choose to cycle in low-cycling contexts. To this end, this research selects individuals from within this group of car-owning middle to high-income adults in Cape Town who do cycle as transport (‘choice’ or intentional cyclists), and examines why they started cycling and what has motivated them to shift and sustain their cycling practice in their adult life. It does so through in-depth interviews with intentional cyclists (n=36) and a survey of individuals (n=36) who share characteristics with the above but who ride as sport only. Interviews were captured as mobility biographies, and segmented in terms of Prochaska and DiClemente’s Transtheoretical or Stages of Change model. Using thematic and narrative analysis, the research considers how cyclists frame the triggers and motivations for adopting, increasing, and maintaining their cycling practice, and whether these motivations differ at different behavioural stages. Qualitative method, and particularly a narrative approach, is well suited to exploring and gaining an in-depth understanding of a specific group of people, such as this group of interest. The research then compares these motivations to the arguments engaged in the advocacy discourse (media, speeches, official policy, civil society activism, letters to the press) regarding the value of bicycle transport and why individuals ‘should’ adopt this mode. Analysis was underpinned by theories of individual behaviour change, including Triandis’ Theory of Interpersonal Behaviour, and Ajzen’s Theory of Planned Behaviour. Key findings are that of the individuals who do cycle as transport, most cycled during childhood; a substantial number kept cycling if they attended university and also for sport. It is rare for an adult new to cycling to use a bicycle as transport. When considering ways to travel other than by car, interviewees were able to draw on memories of the freedom, ‘fun’, and joy of childhood cycling and their current sports practice. They have high levels of self-efficacy and behavioural control (with respect to capability, knowledge, social power, finances, agency), and operate within normative contexts where cycle commuting is either acceptable or encouraged, or where non-normative behaviour identifies them as part of a desired sub-culture. What influences individuals to start a cycling practice, and what influenced them to maintain it, are different. Interviewees initially are drawn to the opportunity to save money on grudge costs such as parking, to avoid driving in traffic, to supplement race training, and to make better use of time. When increasing and sustaining their practice, personal wellbeing is more motivating, as are self-concept and identity. These identities become more entrenched, and increasingly dominant motivations, the more often and for more purposes they ride. Fitness is a motivator across all stages of change. Interviewees most often increase their cycling by seeing, meeting, or riding with others who do so, than they are by other forms of advocacy; the ‘doable’ nature of bicycle transport is a more influential message than the public good that cycling might deliver. What sustains cycling practices is not so much habit but personal identity, commitment, and the wellbeing impact of cycling; where individuals are less identified as cyclists, they appear to be more likely to use their cars when circumstances are challenging. The research finds a mismatch between advocacy and individuals’ motivations, particularly during later stages of cycling behaviour. Advocacy tends to focus on the affordability of cycling, its public health benefits, its ability to ease road traffic congestion, and its social and environmental benefits. These assume altruistic motives for cycling. Among interviewees, the side-effects of carbon mitigation and the opportunity to performatively permeate social divides are welcomed but are not primary motivations. Interviewees enjoy saving money on grudge spend such as parking, but affordability, as such, is not a major concern to this cohort who own their own cars as well as relatively high-end bicycles. Implications for advocacy is that positioning cycling for this cohort as a virtuous activity is not necessarily successful, and that ‘fun’ is a legitimate reason for choosing cycling. Segmenting cyclists by stage of change, and developing interventions that might either catalyze an initial cycling practice or support a longer-term practice, is one approach. Segmenting cyclists by implicit motivation rather than by trip purpose – personal benefit, normative needs, or altruism – is another. Both the theories of Planned Behaviour and of Interpersonal Behaviour have good explanatory potential; the latter more so, as it takes into account the frequency of past behaviour, and the importance of emotion. Interviewees are mostly motivated by personal benefit, and unless an individual loves cycling, they are unlikely to cycle commute, no matter what the benefits might be.